2021
DOI: 10.1016/j.jtcme.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of the hydroethanolic extract of the leaves of Maytenus ilicifolia Mart. Ex Reis

Abstract: Background and Aim Maytenus ilicifolia has analgesic, healing, antioxidant and anti-inflammatory properties. This study evaluated effect of the hydroalcoholic extract of M. ilicifolia leaves on skin wound repair. Experimental procedure Wounds were induced on mice and treated with the extract. The treatment was performed daily, until day 7 after wound induction. Wound closure was measured and the features of the repaired tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Wounds are the most frequent disease in the category of skin and subcutaneous ailments, and in addition to the sanitary damage, non-healing wounds can generate massive expenditures ranging from USD 28.1 to USD 96.8 billion in the United States alone [ 1 , 2 ]. Wounds are defined as a damage in the cellular and anatomical structure of vital tissue, mainly the skin and the surface of internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Wounds are the most frequent disease in the category of skin and subcutaneous ailments, and in addition to the sanitary damage, non-healing wounds can generate massive expenditures ranging from USD 28.1 to USD 96.8 billion in the United States alone [ 1 , 2 ]. Wounds are defined as a damage in the cellular and anatomical structure of vital tissue, mainly the skin and the surface of internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest the influence of C. langsdorffii creams stimulating the wound re-epithelialization mechanism [144]. Similarly, de Moura et al [137] demonstrated that topical treatment with the hydroalcoholic extract of Maytenus ilicifolia Mart. ex Reissek leaves contributes to the advancement of the proliferative stage, probably by increasing the activity of MMP-9.…”
Section: Mechanism Of Actionmentioning
confidence: 88%
“…[52] It is denoted that the leaf from M. ilicifolia is used in the Southern region of Brazil and accelerates the wound healing process. Indeed, recently De Moura and collaborators [53] described that the M. ilicifolia extract accelerated the closure of wounds at a concentration of 4 %, presenting anti-inflammatory effects and hemoglobin increased, along with increased soluble, total, and type III collagens in the wound. In addition, the authors also described that the extract application increased the pro-metalloproteinase (MMP)-9 and MMP9 activity after day 7th of treatment.…”
Section: Petiveria Alliacea L E Maytenus Ilicifolia Mart Ex Reissekmentioning
confidence: 99%